REKONSTRUKSI METODOLOGI PENELITIAN HUKUM DALAM MENGHADAPI DINAMIKA PERKEMBANGAN MASYARAKAT - Dede Imat Nugraha; Hery Chariansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study reconstructs legal research methodology to respond to societal dynamics without abandoning the normative character of legal science. It employs normative legal research with statutory, conceptual, and interdisciplinary approaches. Materials include legislation, books, and journal articles published from 2020 to 2026. Systematic interpretation and thematic synthesis produce a six layer model covering normative orientation, empirical reality, disciplinary integration, technological support, ethical safeguards, and justice evaluation. The model is operationalized through problem diagnosis, mapping of legal materials, evidence design, analysis, integration, prescription, and audit. Technology is treated as a validated instrument rather than a substitute for legal reasoning. The reconstruction strengthens coherence between positive law, social facts, and recommendations while supporting transparent, reviewable, and substantively just legal scholarship.